Pusa Shakti (DT-19): Promising tomato variety for summer cultivation and long-distance transport - Yadav, R K; Tomar, B S; Chaudhary, H; Lata, Suman; Jat, Gograj Singh; Nirankar (Indian Horticulture, 2025)
Pusa Shakti (DT-19) is a newly developed indeterminate tomato variety from ICAR–IARI, Pusa, New Delhi, identified for release during the 42nd AICRP-VC Group Meeting (2024) for Zone V and notified vide S.O. 4917(E), dated 13 November 2024. It is tolerant to high temperatures, suitable for cultivation from October to May under open-field conditions. Fruits are round, deep red, with thick pericarp(7.0 mm), average weight of 80 g, 4.8 °Brix TSS, and 6.0 mg/100 g lycopene. With an average yield of 352 q/ha and potential exceeding 450 q/ha, this variety offers extended summer fruiting and long-distance transportability, enhancing farmer profitability.